Capacities of local maize seed enterprises in Mexico: Implications for seed systems development - Donovan, Jason; Rutsaert, Pieter; Domínguez, Ciro; Peña, Meliza (Springer, 2022)
Where maize plays a critical role in food security, governments and donors have invested heavily in support of local, privately owned, often small and medium sized, maize seed enterprises (maize SMEs). Underpinning these investments are strong assumptions about maize SMEs’ capacity to produce and distribute seed to smallholders. This study assesses the capacities of 22 maize SMEs in Mexico that engaged with MasAgro—a large-scale development program initiated in 2011 that has provided maize SMEs with improved genetic material and technical assistance. Data were collected onsite from in-depth interviews with enterprise owners and managers and complemented with other primary and secondary sources. Overall, maize SMEs showed high levels of absorptive capacity for seed production, but limited signs of learning and innovation in terms of business organization and strategic seed marketing. Asset endowments varied widely among the SMEs, but generally they were lowest among the smaller enterprises, and access to business development services beyond MasAgro was practically nonexistent. Results highlighted the critical role of MasAgro in reinvigorating the portfolios of seeds produced by maize SMEs, as well as the challenges ahead for maize SMEs to scale the new technologies in a competitive market that has long been dominated by multinational seed enterprises. Among these challenges were limited investment in seed marketing, weak infrastructure for seed production, and limited experience in business management. Achieving the food security goals through maize SMEs will require making national maize seed industry development a strategic imperative.